Effect of nano-potassium and chemopreservation on the vegetative system of mallow Malva sylvestris L (Journal of the College of Basic Education, 2026)
The experiment was conducted during the 2025-2026 season in Dhi Qar Governorate / Qalat Sukkar / Al-Salam District to determine the effect of nano-potassium and biofertilizer on mallow plants. The experiment was designed using a Randomized Complete Block Design (RCBD) with three replicates, including five concentrations of nano-potassium (125, 100, 75, 50, 0) ml/L and five concentrations of biofertilizer (6, 4, 2, 1, 0) g/L. The results of treating the plants with nano-potassium showed a significant increase in the studied traits. The results showed that a concentration of 125 ml/L of nano-potassium achieved the highest significant increase in plant height, stem diameter, number of branches per plant, and leaf area. The high concentration of nano-potassium also caused a significant increase in the number of leaves. Furthermore, treating the plants with biofertilizer had a positive effect on the studied traits. A concentration of 6 g/L of biofertilizer resulted in a significant increase in plant height, stem diameter, number of branches, leaf area, and number of leaves. The interaction between treatments showed a significant increase in most of the studied traits, especially with the combination of 125 ml/L of nano-potassium and 6 g/L of biofertilizer